Evidence for loss and reacquisition of alcoholic fermentation in a fructophilic yeast lineage - Gonçalves, Carla (eLife, 2018)
Fructophily is a rare trait that consists of the preference for fructose over other carbon sources. Here, we show that in a yeast lineage (the Wickerhamiella/Starmerella, W/S clade) comprised of fructophilic species thriving in the high-sugar floral niche, the acquisition of fructophily is concurrent with a wider remodeling of central carbon metabolism. Coupling comparative genomics with biochemical and genetic approaches, we gathered ample evidence for the loss of alcoholic fermentation in an ancestor of the W/S clade and subsequent reinstatement through either horizontal acquisition of homologous bacterial genes or modification of a pre-existing yeast gene. An enzyme required for sucrose assimilation was also acquired from bacteria, suggesting that the genetic novelties identified in the W/S clade may be related to adaptation to the high-sugar environment. This work shows how even central carbon metabolism can be remodeled by a surge of HGT events.